Contemporary art, world cinema, and visual culture essays - Dabashi, Hamid 1951- (Anthem Press, 2019)
"The volume contains the collection of essays on modern and contemporary arts by Hamid Dabashi, the acclaimed cultural critic and scholar of Middle Eastern history and culture. It reintroduces the work of one theorist of modern and contemporary arts to extrapolate more universal issues of concern to art criticism in general"--
Keywords: Film; Kunst; Arts, Modern / 20th century / Themes, motives; Arts, Modern / 21st century / Themes, motives; Arts and society / History / 20th century; Arts and society / History / 21st century; ART / Criticism & Theory; ART / Middle Eastern; LITERARY CRITICISM / Middle Eastern; Arts and society; Arts, Modern / Themes, motives; 1900-2099; History; Aufsatzsammlung